Investigation of carbon-based solid acid catalyst from Jatropha curcas biomass in biodiesel production. (15th July 2017) - Mardhiah, H. Haziratul; Ong, Hwai Chyuan; Masjuki, H.H.; Lim, Steven; Pang, Yean Ling
Graphical abstract: Highlights: Waste Jatropha curcas seed cake was utilized as catalyst in esterification process. Maximum conversion yield achieved was 99.13% at optimized reaction parameter. Catalytic ability was superior compared to the conventional sulfuric acid catalyst. Catalyst is reusable up to the fourth cycle with slight decrease in yield. Abstract: In this study, a carbon-based solid acid catalyst was prepared using the de-oiled Jatropha curcas (JC) seed cake waste. The catalyst was consequently used to esterify the JC oil in order to lower the high free fatty acid content (FFA) to an acceptable level (<4 mg KOH g −1 ) for biodiesel production. The chemical and physical properties of the catalyst were characterized using a variety of techniques. The conversion of FFA reached 99.13% under optimum conditions of 12:1 methanol/oil molar ratio, 7.5 wt% catalyst loading, 60 min reaction time and 60 °C reaction temperature at 350 rpm. The catalyst was also determined to outperform the conventionally used sulfuric acid catalyst in terms of reaction time needed to achieve the highest conversion yield. The high catalytic ability of the catalyst was associated with the high acid site density formed in the catalyst which was due to the high porosity and large pore size of the carbon framework of the catalyst. The hydrophobic nature of the catalyst also contributed to the stability of the catalyst in which it can be re-used up until the 4th cycle. The recyclability of the catalyst and its cheap feedstock makes the overall process much simpler, cost-efficient and environment-friendly.